(3eNJUQ TYH GdEjeGfs - (3CHhMaU YeQ GdbRhjfjs; (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3hHYO abO JcQQ ef HYV cHGQ GdYdeGA YOI ecJhHGJ ef hGSW Edi HZOGO aj GdSDGd Yf YOO TYH GdEjeGf s
(3BNQgG (B:s
(3bd COYhG GdPjf RYeJe ef Ohfg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1047 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B574s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs